Executive Committee Minutes 2009-11-19 - Academic Senate:::::::::
Academic Technology update, Resolution Establishing a Senate Diversity Committee, March 2nd as a Furlough Day, Move of Linguistics program from Anthropology to English, New Policy on Double Majors